Role of iRhoms 1 and 2 in Endochondral Ossification - Fang, Renpeng (Int J Mol Sci, 2020)
Growth of the axial and appendicular skeleton depends on endochondral ossification, which is controlled by tightly regulated cell–cell interactions in the developing growth plates. Previous studies have uncovered an important role of a disintegrin and metalloprotease 17 (ADAM17) in the normal development of the mineralized zone of hypertrophic chondrocytes during endochondral ossification. ADAM17 regulates EGF-receptor signaling by cleaving EGFR-ligands such as TGFα from their membrane-anchored precursor. The activity of ADAM17 is controlled by two regulatory binding partners, the inactive Rhomboids 1 and 2 (iRhom1, 2), raising questions about their role in endochondral ossification. To address this question, we generated mice lacking iRhom2 (iR2−/−) with floxed alleles of iRhom1 that were specifically deleted in chondrocytes by Col2a1-Cre (iR1∆Ch). The resulting iR2−/−iR1∆Ch mice had retarded bone growth compared to iR2−/− mice, caused by a significantly expanded zone of hypertrophic mineralizing chondrocytes in the growth plate. Primary iR2−/−iR1∆Ch chondrocytes had strongly reduced shedding of TGFα and other ADAM17-dependent EGFR-ligands. The enlarged zone of mineralized hypertrophic chondrocytes in iR2−/−iR1∆Ch mice closely resembled the abnormal growth plate in A17∆Ch mice and was similar to growth plates in Tgfα−/− mice or mice with EGFR mutations. These data support a model in which iRhom1 and 2 regulate bone growth by controlling the ADAM17/TGFα/EGFR signaling axis during endochondral ossification.